Determination of the Pollution Levels of Waste Water from Nakuru Tanners, Kenya - Nyabaro , Obed M.; Muthoka , Titus M.; Mosoti , Douglas (African Journal of Education,Science and Technology (AJEST), 2025)
Wastewater from leather processing industries is very complex and leads to water pollution if discharged before treatment, especially due to its high organic loading and chromium content. Over the past years, Nakuru Tanners Ltd has been discharging raw effluents into the Ndarugo River causing pollution of surface waters, groundwater and soil. Since the water from this river is used for drinking, agricultural and industrial purposes, the assessment of the effluents is necessary. A study to determine the level of toxicants in Nakuru tannery wastewater discharged to the environment was undertaken. Water samples from four sampling points (S1 – Pre-tanning Stage, S2 – Tanning Stage, S3 – Post-tanning Stage and S4 – Drainage to the river) were collected and analyzed. A comprehensive experimental evaluation of tannery wastewater was performed as a basis for the determination of the levels of different pollutants , BOD, COD, pH, turbidity, TSS, NO3- and NO2- and the values obtained were compared to the standards set by NEMA and WHO. The levels of the metals chromium, iron and lead were determined using FAAS, Kjeldahl method was used for the quantization of NO3-, NO2- and P determined by Mehlich II extraction while UV-Vis was used in colour determination. The results show that sampling point S1 (wastewater from the pre-tanning stage) recorded the highest parameter levels for pH, TSS and SO42- of 11, 294.40 mg/L and 318.50 mg/L, respectively. Sampling point S2 had the highest levels of COD, BOD, Cr and Pb with corresponding values of 9,107 mg/L, 9,150 mg/L, 945 µg/L and 6.50 mg/L. Sampling point S3 recorded the highest parameters of temperature, DO, Fe, P and electrical conductivity of values 24.62 0C, 1.15 mg/L, 5.40 mg/L, 12.40 mg/L and 14720 µSCm-3 while S4 recorded the highest of NO3 - and NO2-pollutants with respective values of 85.20 mg/L and 146.70 mg/L. These levels were, however, above the recommended values set by WHO and NEMA for such parameters in tannery waste water. The company should therefore take immediate counteractive actions to lower these levels of the toxicants in order to avert the associated effects to human and environment. This study has made various recommendations which if undertaken will help make the tannery effluents safe before di sposal.